A ROUGH PATH TOWARDS A THEORETICAL APPREHENSION OF KOREAN ASPECT - BAŃCZEROWSKI, Jerzy (International Journal of Korean Humanities and Social Sciences, 2016)
Having considered some general aspectological and aspect-methodological problems, the author proceeds to the discussion of certain selected questions concerning Korean aspectology, in particular, an interaction between aspect and momentarity/ progressivity as well as aspective-lingual reasoning. The position of the category of aspect within grammar is revisited of and the problem of formulation of aspectological theories is addressed. The proposed theoretical apprehension of the relation of Korean aspect to momentarity/progressivity and the aspective-lingual deduction are treated rather briefly.